Contradiction Implications of the Receptie a Contrario Theory in Minangkabau Inheritance - Hazar Kusmayanti; Dede Mulyanto; Deviana Yuanitasari; Muhammadafeefee Assalihee (Justicia Islamica, 2024)
This research explores the application of the receptie a contrario theory in its implementation in the inheritance law of the Minangkabau customary society. This research is a normative juridical research with conceptual and philosophical approaches. Data source analysis is conducted on primary legal materials in the form of expert interviews and laws and regulations, and secondary legal materials in the form of research results on Islamic law and customary law. Based on the research results, it can be concluded that the theory of receptie a contrario still applies to inheritance issues in Minangkabau. Although the Minangkabau people are famous for their adherence to customs, they consider breaking customs shameful. However, the Minangkabau community has explicitly stated that their customary inheritance law refers to Islamic inheritance law by recognizing that children and wives are heirs of their parents/husbands. In contrast, previously, the customary heirs recognized were nieces (kemenakan). This research confirms that the application of the receptie a contrario theory still applies to inheritance issues in Minangkabau. In addition, it also contributes to explaining to the broader community that inheritance in Minangkabau, although it adheres to matrilineal kinship lines, has implemented Islamic law.